Obitelj dalmatinskog plemstva od 12. do 14. stoljeća - Nikolić Jakus, Zrinka (Acta Histriae, 2008)
In the period from the twelfth until the fourteenth century the Dalmatian noble family gradually was established as a patrilineal lineage. In the article this process is studied especially on the example of the three biggest Dalmatian cities - Zadar, Trogir, and Split. The changes first appearedin Zadar. They appeared relatively late in the terminology connected with family - at the end of the thirteenth century - and they are best seen in the change of status of daughters in relations to family inheritance. Although by Roman law they had rights to equal shares in the whole property - including estates and houses - just the same as their brothers, during the thirteenth century the right of inheritance after the death of the parents was gradually replaced by a pay-off of shares of inheritance in the dowry at the time of marriage. First, the payment of inheritance in money in the dowry was preferred when girls married foreigners from distant cities. This new custom appeared first in Zadar because it had a more developed economy, making monetary payments easier. The practice of giving estates in dowries was retained longer in Trogir and Split. Patronage rights were never denied to female descendants. Finally, in fourteenth-century Zadar, payment of dowries in cash became a way to deny sisters an equal share in inheritance with brothers, because dowries fell short of equal shares of the inheritance. That patrilineal lineage was getting stronger is also illustrated by the adoption of family names. It is significant that family names that derived from the name of ancestors appeared later, while the first family names derived from nicknames. In this process Zadar was also ahead of other cities. In spite of the attenuated process of the establishment of the patrilineal family, the importance of cognatic and affinial ties were continuously recognised in private and public life whether in legal attempts to prevent the uniting of cousins in governmental bodies or in the obligation of cognates to take part in the defense of family honor and feuds. In this way, both types of family - cognatic and agnatic - had an important role in the circles of Dalmatian nobility.
Keywords: Dalmacija; Dalmatia; družina; family; mesta; mestno plemstvo; Middle Ages; plemstvo; Split; srednji vek; Trogir; Zadar